2012
DOI: 10.1016/j.atherosclerosis.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum fatty acid composition and desaturase activity to C-reactive protein in Japanese men and women

Abstract: a b s t r a c tBackground: Although fatty acid composition in serum and desaturase activity, which alters serum fatty acid composition, has been associated with C-reactive protein (CRP) concentration in Western populations, no study has been carried out in non-Western populations. We examined the association of serum fatty acids and estimated desaturase activity with CRP concentrations in Japanese men and women. Methods: Subjects were 489 Japanese municipal employees aged 21-67 years who participated in a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Data used in this study are derived from a 2006 health survey among employees of two municipal offices in northeastern Kyushu, Japan, as described elsewhere [25,26]. In brief, at the time of the periodic health examination, all full time workers (n = 601) except those on long sick or maternity leave were invited to the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Data used in this study are derived from a 2006 health survey among employees of two municipal offices in northeastern Kyushu, Japan, as described elsewhere [25,26]. In brief, at the time of the periodic health examination, all full time workers (n = 601) except those on long sick or maternity leave were invited to the survey.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a prospective cohort of 395 Portuguese, neither palmitic nor stearic acid intake was associated with CRP [35]. In a cross-sectional survey among 489 healthy Japanese adults, CRP was found to have a significant and positive association with serum palmitic but not stearic acid, and this relationship was only observed in men [38]. In another cross-sectional study of 528 young Canadian adults, CRP was found to have a significant and positive association with plasma palmitic acid but a significant and inverse association with stearic acid; these correlations were only observed in women and were independent of ethnicity [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, such effects may be relevant in the Japanese study including school children with a mean age of around 11 y but are improbable in our sample of young and thus mostly prepubertal children. In 489 Japanese adults, serum CRP concentration was inversely associated with D5D in men and women (32).…”
Section: Association Of Desaturase Activity and Crp In European Childrenmentioning
confidence: 98%